2019
DOI: 10.3390/plants9010024
|View full text |Cite
|
Sign up to set email alerts
|

High Light Acclimation Induces Chloroplast Precursor Phosphorylation and Reduces Import Efficiency

Abstract: Acclimation is an essential process in plants on many levels, but especially in chloroplasts under changing light conditions. It is partially known how the photosynthetic machinery reacts upon exposure to high light intensities, including rearrangement of numerous protein complexes. Since the majority of proteins residing within chloroplasts needs to be posttranslationally imported into the organelles, we endeavored to study how this important process is regulated upon subjecting plants from pea and Arabidopsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…(6) Transport processes across the inner membrane of the chloroplast envelope are adjusted in response to low temperatures (Guan et al ., 2019; Trentmann et al ., 2020). (7) Fine‐tuning of chloroplast protein import contributes to effective plant development and acclimation (Lamberti et al ., 2011; Eisa et al ., 2019a; Eisa et al ., 2019b).…”
Section: Ra2 Metabolism: Metabolic Changes That Promote Acclimation mentioning
confidence: 99%
See 1 more Smart Citation
“…(6) Transport processes across the inner membrane of the chloroplast envelope are adjusted in response to low temperatures (Guan et al ., 2019; Trentmann et al ., 2020). (7) Fine‐tuning of chloroplast protein import contributes to effective plant development and acclimation (Lamberti et al ., 2011; Eisa et al ., 2019a; Eisa et al ., 2019b).…”
Section: Ra2 Metabolism: Metabolic Changes That Promote Acclimation mentioning
confidence: 99%
“…Our consortium recently showed that S ‐adenosyl methionine and isoleucine – both of which are synthesised in the chloroplast – bind to the highly conserved STY‐specific aspartate kinase–chorismate mutase–tyrA domain, which leads to the inhibition of kinase activity (Eisa et al ., 2019a). In addition, rates of precursor protein import are reduced under high light conditions owing to a decrease in the expression of the STY kinase genes (Eisa et al ., 2019b). In summary, the regulation of chloroplast protein import by phosphorylation of precursor proteins is an interesting but incompletely understood facet of metabolic acclimation to challenging stimuli (process 7 in Figure 2).…”
Section: Ra2 Metabolism: Metabolic Changes That Promote Acclimation mentioning
confidence: 99%
“…It has been shown that phosphorylation of chloroplast-designated preproteins by cytosolic kinases is one of the key steps ensuring their sorting and specific targeting to this organelle during plastid maturation and stress response in Arabidopsis and pea ( Waegmann and Soll, 1996 ; Martin et al, 2006 ; Lamberti et al, 2011b ; Zufferey et al, 2017 ; Eisa et al, 2019 ; Hristou et al, 2020 ). The serine/threonine/tyrosine kinase 8 (STY8), STY17, and STY46 kinases phosphorylate chloroplast preprotein transit peptides ensuring their binding of a 14–3–3 dimer, which enhances association to the TOC receptor located at the outer envelope membrane of the chloroplast ( Martin et al, 2006 ; Lamberti et al, 2011a, 2011b).…”
Section: Discussionmentioning
confidence: 99%
“…The average partitioning proportions of stems (62.9 ± 1.9%) in the natural environment were ~7.0% higher than those found in plantations (56.0 ± 4.4%) due to having ~2 m more in average tree total height across the same ranges of D ( Table 1 ). These results might indicate that the natural Korean pine trees obtained lower light intensities compared to those grown in plantations [ 55 , 56 , 57 ]. As the “functional equilibrium” theory explained that if the limiting factor is located above-ground, plants will relatively allocate more biomass in shoots (i.e., foliage, branch, and stem), and vice versa if the growth limiting factor is located below-ground [ 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%